HETEROCHRONY OF GAUDI'S ARCHITECTURE - Kiuntsli, R.; Stepaniuk, A.; Besaha, I. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Today in the scientific literature there are active discussions about the architectural style of the Sagrada Familia Cathedral. Gaudi’s architecture is often referred to as organic or bionic. The presence of the bionic style in Gaudi’s architecture is supported by the fact that the Sagrada Familia has complex shapes, which are known today as helicoids, hyperboloids and hyperbolic paraboloids. Gaudi borrows these forms from nature and bases the construction of columns, vaults and other structural elements of the temple. However, the architectural image of the Sagrada Familia was also influenced by Gaudi’s existential experiences, which were the result of many factors. First of all, it is the emotional experiences of childhood. Other important factors in shaping the image of the Sagrada Familia were Catalan modernism, which emerged at the turn of the 19th – 20th centuries in Barcelona, the influence of German Expressionism, the interaction of contemporary Gaudi architects and the influence of Goethe’s philosophy on A. Gaudi. Goethe’s organic worldview, which was based on the understanding of the world as a living monadic whole, revolutionized not only philosophy but also architecture. The fundamental principle of the Sagrada Familia is a kind of proteism, the desire for constant renewal, expressed through both the interior and exterior of the building. The transformation of living integral formations, depicted on the three facades of the Sagrada Familia, demonstrates a series of metamorphoses of pra-phenomenon (Urphanomen – germ. after Goethe) and metamorphosis of the human soul under the influence of Christ’s teachings. Antonio Gaudi’s architecture is special for its emotional content, which hides the author’s emotional conflicts and contradictions. Opposing one to the natural environment and emphasizing harmonious coexistence with it is an oxymoron that the author laid down in the architectural forms of the Sagrada Familia. The Church of the Holy Family can be seen as a symbiosis of advanced technology and creative expression, the skill of presenting the author’s architectural ideas and happy coincidences. The artist's original vision and understanding of the relationship between the anthropogenic and natural environment in the creation of architectural space, the place and role of man in this process determined his exclusively individual architectural style.